A discourse analysis of the introduction of m.a. Theses in english linguistics in vietnam and australia - Trần Thị Ngọc Phương (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Based on the theories of discourse analysis, this study focused on describing and analyzing typical discourse features of English language master thesis introductions in Australia (A-ELMTIs) and English language master thesis introductions in Vietnam (V-ELMTIs) in terms of the layout, syntactic features, lexical features and cohesion devices. From the investigation, we found out their differences and similarities. Firstly, the layout analysis showed that both A-ELMTIs and V-ELMTIs provided an overview of the content of the thesis, but the approaches that were adopted were significantly different. V-ELMTIs followed a far more fixed structure, and detailed headings were used while in A-ELMTIs, headings were used far less, and information that was clearly stated in the Vietnamese theses tended to be more implicit than in the Australian ones. With regard to syntactic features, it was evident that the largest differences were in the use of simple and compound sentences. Simple sentences were used with far greater frequency in V-ELMTIs than in A-ELTMIs, whereas there was more use of complex sentences in A-ELTMIs. With regard to cohesion;l, A-ELMTIs and V-ELMTIs showed some similar trends in applying cohesion devices that reference and conjunction are dominant. Regarding lexical cohesion, there is a strong similarity between A-ELMTIs and V-ELMTIs that repetition which was regularly used, followed by synonyms with quite medium and next super ordinate with the smallest percentage. Finally, lexical features, A-ELMTIs used a higher proportion of “contrast terms” and “quantifiers and quasi negatives” than that of V-ELTMIs, namely “contrast terms”. Although “negatives” were applied at a very low rate by both, V-ELMTIs used one more instance than A-ELMTIs. On the basis of the findings, some implications for teaching and learning writing skills were suggested.